2021
DOI: 10.1002/apj.2616
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on kinetic characteristics of oil sludge gasification

Abstract: Oil sludge (OS) is a typical dangerous waste in petroleum industry, which also contains abundant energy. The purpose of this study was to recover resources from OS gasification. To figure out the gasification process, a thermal analyzer was used to carry out OS gasification experiments under steam/nitrogen atmosphere with different heating rates. Results showed that the OS gasification reaction could be divided into five stages: free water volatilization, the escape of light components, the cracking of heavy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
2
Order By: Relevance
“…According to the physicochemical composition and method of formation, oil sludge is divided into five groups [32][33][34]: (iv) Tank oil sludge is waste generated throughout the transportation and storage of oil in various tanks. (v) Ground oil sludge -is a product of the combination of soil and oil spilled on it; the reason for this can be both a technological process and an accident.…”
Section: ■ Formation Of Oil Sludgementioning
confidence: 99%
“…According to the physicochemical composition and method of formation, oil sludge is divided into five groups [32][33][34]: (iv) Tank oil sludge is waste generated throughout the transportation and storage of oil in various tanks. (v) Ground oil sludge -is a product of the combination of soil and oil spilled on it; the reason for this can be both a technological process and an accident.…”
Section: ■ Formation Of Oil Sludgementioning
confidence: 99%
“…Oil is one of the most abundant energy resources worldwide [1]; its extraction, transportation, storage, and processing are associated with the formation of a significant amount of waste, including oil sludge (OS) [2][3][4][5][6][7]. This type of high-hazard waste comprises water, oil, mineral impurities, and different deposits (sand, clay, silt, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was described by Motlang et al [25] based on numerical studies of the effect of water vapor added in OS thermal conversion. In turn, Chu et al [5] revealed five stages of steam pyrolysis of OS proceeding in the temperature range of 30-669 • C: drying of external moisture, volatilization of light components, cracking of heavy components and steam reforming, the coking process, and the subsequent inorganic mineral decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время нефть является одним из наиболее востребованных видов энергоносителей в мире [1]. Её добыча, транспортировка, хранение и переработка сопровождаются образованием значительного количества нефтешламовых отходов [2][3][4], имеющих высокий класс опасности [3]. Состав нефтешламовых отходов зависит от своего технологического происхождения.…”
unclassified
“…Одним из современных подходов переработки нефтешламовых отходов является их термическое преобразование методами пиролиза или газификации [2][3][4]7] с получением полезных продуктов в виде жидких углеводородов, синтез-газа и углеродистого остатка. Перечисленные процессы относятся, как правило, к аллотермическому типу [8], по причине чего образующийся углеродистый остаток используют в качестве вторичного энергоресурса для компенсации энергетических затрат.…”
unclassified